From public preferences to clinical tasks in anti‐amyloid therapy for Alzheimer's disease - Kyohei Otani (Psychiatry and Clinical Neurosciences, 2026)
Tajika and colleagues found that, among Japanese respondents willing to consider lecanemab, the median smallest worthwhile difference exceeded the absolute benefit used in their study scenario. This commentary argues that this expectation–efficacy gap should be translated into concrete clinical tasks across the anti‐amyloid care pathway, including expectation assessment, biomarker and eligibility counseling, shared decision‐making, treatment monitoring, support for non‐initiation or discontinuation, and continuing psychosocial care.